The Moderating Effect of Earning Quality on Financial Distress Prediction of Companies Listed in Tehran Stock Exchange - Gholamreza Mansoorfar; Farzad Ghayoor; Maryam Asadi (راهبرد مدیریت مالی, 2017)
One of the threats facing the companies is the financial distress and the bankruptcy accordingly. The purpose of this study is to investigate the effect of earning quality as a moderator in companies’ financial distress prediction. The population of study included 41 distressed and 41 non distressed companies listed in Tehran Stock Exchange during 2003 to 2013. The selection criterion to choose distressed companies was the use of five specific criteria for financial distress. Firstly, to verify the separation accuracy of two samples, distress and Non-distress, using the Wilcoxon test, the average of two independent variables were analyzed. In order to investigate the financial distress prediction, three models included Altman, Ohlson and Bharath and Shumway in a binary logistic regression were used. The findings of the study show that the earning quality significantly increases the accuracy of predicting financial distress.  Also Altman model, in comparison to other models, is more accurate in predicting financial distress, so it is considered as a more suitable tool in prediction.